Učbeniški skladi - Kodrič-Dačić, Eva (Knjižnica, 2021)
The textbook rental collection is a separate part of a school library, which provides teaching materials for pupils and students and records current teaching materials used in educational institutions. Although it has had a long tradition, the operation proce-dures of textbook rental collection were first defined by regulations in 1994, and it was not until 2017 that school librarians formally became their trustees. Textbook rental collections have been challenged by teachers, publishers and librarians, but they are a useful part of a school library, given the number of students who borrow textbooks from them. The article presents a brief overview of the development of textbook rental collections in Slovenian schools and analyzes data concerning scope and use of text-books provided by statistical measurements and a survey on the tasks of school librar-ians collected by the National and University Library of Slovenia and the Institute of Information Science.
Keywords: Slovenija; šolske knjižnice; učbeniki; učbeniški skladi